Resting-state Dynamics as a Cortical Signature of Anesthesia in Monkeys. (November 2018) - Uhrig, Lynn; Sitt, Jacobo D.; Jacob, Amaury; Tasserie, Jordy; Barttfeld, Pablo; Dupont, Morgan; Dehaene, Stanislas; Jarraya, Bechir
Editor's Perspective: What We Already Know about This Topic: Anesthesia-induced loss of consciousness is paralleled by a disruption of frontoparietal functional correlation, as measured by functional magnetic resonance imaging and electroencephalography. However, it is still unclear how anesthesia induces such a corticocortical disconnection. Dynamic-resting state is a recent analytical method to study large-scale brain networks, allowing the clustering of functional magnetic resonance images into functional brain states. What This Article Tells Us That Is New: When moving from wakefulness to anesthesia, the anatomical structure of connections between brain areas becomes the main driver of the repertoire of functional states. Subjects given anesthesia lose the ability to generate flexible functional brain states that transcend brain anatomy. High similarity between brain structure and function is a new general signature of anesthesia-induced loss of consciousness. Background: The mechanism by which anesthetics induce a loss of consciousness remains a puzzling problem. We hypothesized that a cortical signature of anesthesia could be found in an increase in similarity between the matrix of resting-state functional correlations and the anatomical connectivity matrix of the brain, resulting in an increased function-structure similarity. Methods: We acquired resting-state functional magnetic resonance images in macaque monkeys during wakefulness (n = 3) or anesthesia with propofol (n = 3), ketamine (n = 3), or sevoflurane (n = 3). We used the k-means algorithm to cluster dynamic resting-state data into independent functional brain states. For each condition, we performed a regression analysis to quantify function-structure similarity and the repertoire of functional brain states. Results: Seven functional brain states were clustered and ranked according to their similarity to structural connectivity, with higher ranks corresponding to higher function-structure similarity and lower ranks corresponding to lower correlation between brain function and brain anatomy. Anesthesia shifted the brain state composition from a low rank (rounded rank [mean ± SD]) in the awake condition (awake rank = 4 [3.58 ± 1.03]) to high ranks in the different anesthetic conditions (ketamine rank = 6 [6.10 ± 0.32]; moderate propofol rank = 6 [6.15 ± 0.76]; deep propofol rank = 6 [6.16 ± 0.46]; moderate sevoflurane rank = 5 [5.10 ± 0.81]; deep sevoflurane rank = 6 [5.81 ± 1.11]; P < 0.0001). Conclusions: Whatever the molecular mechanism, anesthesia led to a massive reconfiguration of the repertoire of functional brain states that became predominantly shaped by brain anatomy (high function-structure similarity), giving rise to a well-defined cortical signature of anesthesia-induced loss of consciousness. Abstract : When moving from wakefulness to anesthesia, the anatomical structure of connections between brain areas becomes the main driver of the repertoire of functional states. Subjects given anesthesia lose the ability to generate flexible functional brain states that transcend brain anatomy. High similarity between brain structure and function is a new general signature of anesthesia-induced loss of consciousness.Supplemental Digital Content is available in the text.